Adversarial economic preferences predict right-wing voting - Thomas Buser (Tinbergen Institute, 2024)
I analyze Dutch panel data that contains rich information on voting, political opinions, and personality traits. I show that "adversarial" preferences - competitiveness, negative reciprocity, distrust, and selfishness - are strong predictors of right-wing and populist political preferences. Their explanatory power is similar to that of a rich set of socioeconomic status indicators - including income, education and occupation - and robust to non-parametrically controlling for them. I replicate previously studied associations between classic personality traits and political preferences, and show that adversarial preferences predict voting independently from these traits - and often with larger effect sizes. The complex Dutch party landscape allows me to go further than simple left-right comparisons to differentiate parties along an economic left-right axis, a social progressive-conservative axis, and a populism axis. Competitiveness predicts voting for economically right-wing parties, whereas negative reciprocity, distrust, and selfishness are stronger predictors of voting for socially conservative and populist parties.
Keywords: D72; D9; J16; 330; voting; political preferences; personality; competitiveness; reciprocity